FREKUENSI GEN CUPING MELEKAT, ALIS MENYAMBUNG, LESUNG PIPI DAN LIDAH MENGGULUNG PADA MASYARAKAT DESA SUBAYA, KECAMATAN KINTAMANI, KABUPATEN BANGLI - Mirayanti, Yulia; Junitha, I Ketut; Suaskara, Ida Bagus Made (SIMBIOSIS, 2017)
This study was conducted to find out the determinant allele frequencies and variations of characteristics of face and earlobe, based on the presence or absence of attached earlobes, connected eyebrows (unibrow), dimples, and tongue-rolling on Subaya village people, Kintamani, Bangli. In this study, 100 samples of proband (67 men and 33 women) as the research data were tested by using Chi-Square Test. Then, the data were analyzed by pedigree diagram to each family. The results of study show that 19% of people have the characteristic of attached earlobes, 12% of people have the characteristic of connected eyebrows, 7% of people have the characteristic of dimples, and 16% of people have the characteristic of tongue-rolling. The highest gene frequency value is the characteristic of attached earlobes (0,43), then, followed by the characteristics of connected eyebrows (0,34) and tongue-rolling (0,084) as well as the lowest gene frequency is the characteristic of dimples (0,036). Keyword s: autosomal inheritance, genetic variation, Subaya village, inbreeding